(untitled) (Heritage, 2025)
This paper analyzes the sustainability of the custom of offering farmers’ candles (ratarske sveće) to the Tronoša Monastery as an element of intangible cultural heritage. The research shows that, in the past, this tradition was entirely under the authority of the local community, which independently organized all related activities. However, in recent decades, representatives of the Serbian Orthodox Church – primarily the monks from the Tronoša Monastery – have assumed a significant role in preserving the custom, acting as custodians and organizers of the ritual. During field research conducted in 2022, it was established that the custom, although stripped of its former magical and agrarian functions, continues to exist as a religious ritual, primarily due to the institutional support of the Orthodox Church and the spiritual motivation of the participants. It has also been established that church authorities, in addition to organizing customs, also contribute to the interpretation of customs in a religious context and provide religious legitimation to the entire ritual. At the same time, the paper highlights certain risks associated with this model of sustainability. Reliance on the personal authority of individual clergy members raises concerns about the future of the custom. Although institutional support enables the preservation of the form, the paper problematizes the possible loss of control of the local community over its own heritage and the narrowing of space for intergenerational transmission without the help of representatives of the Serbian Orthodox Church. The paper concludes that ensuring the sustainability of the custom requires a balance between institutional authority and active local community participation, along with the involvement of younger generations. The ritual of making and lighting farmers’ candles stands as an example of successful cultural transformation, but also as a reminder of the complex power dynamics embedded in the processes of safeguarding intangible cultural heritage.